Chromophore equilibria in bacteriorhodopsin. - Fischer, U (1979)
An investigation of the dark equilibria between different chromophores of bacteriorhodopsin (BR) and studies of the kinetics of their interconversion and photochemical activity have led to the following conclusions. (a) A component of the 605-nm chromophore of BR decays in the millisecond range and is likely to be identical to the intermediate O of the photochemical cycle of BR and is assumed to be formed from the purple complex (PC) by the binding of one proton to BR. (b) An acidic form the PC, PCaL-, arises from the 605-nm chromophore by selective binding of anions L- (F- greater than Cl- greater than Br- greater than I- greater than Cl04-) to BR. (c) The isomeric equilibrium between 13-cis and all-trans retinal is approximately 0.15/0.85 in PCaCl-, 0.3/0.7 in the 605-nm chromophore as compared to 0.5/0.5 in the PC. (d) The 500-nm chromophore is formed from the PC by release of nearly one proton from BR. (e) The pH range in which the PC exists is reduced in a high-temperature structure of the purple membrane as compared to its low temperature structure. A model for the chromophore structure is proposed as a hypothesis, which allows a comprehensive interpretation of the results. In this model the absorption spectrum of the retinylidene lysine Schiff base is modulated by its protonation state and the interaction with an anionic group.